Innovation offshoring and reshoring with fully endogenous growth. - Davis, Colin; Hashimoto, Ken‐ichi (Southern Economic Journal, 2023)
This paper studies the implications of innovation offshoring and reshoring for long‐run productivity growth in a North–South framework that features a tension in the firm‐level innovation location decision between accessing technical knowledge in an asset‐wealthy country and sourcing low‐cost high‐skilled labor in an asset‐poor country. We show that, with trade costs and imperfect international knowledge diffusion, industry and innovation tend to concentrate geographically in proximity to the larger market of the asset‐wealthy North when trade costs are high. Investigating the effects of greater economic integration, we find that an improvement in knowledge diffusion increases the share of firms offshoring innovation to the asset‐poor South to take advantage of lower high‐skilled wages, potentially raising the rate of productivity growth. A decrease in trade costs, however, induces firms to reshore innovation to the asset‐wealthy North to take advantage of greater knowledge spillovers, with rising high‐skilled wages potentially lowering the productivity growth rate.